Enhanced mast cell activation in mice deficient in the A2b adenosine receptor - Hua, Xiaoyang (The Rockefeller University Press, 2007)
Antigen-mediated cross-linking of IgE bound to mast cells via the high affinity receptor for IgE triggers a signaling cascade that results in the release of intracellular calcium stores, followed by an influx of extracellular calcium. The collective increase in intracellular calcium is critical to the release of the granular contents of the mast cell, which include the mediators of acute anaphylaxis. We show that the sensitivity of the mast cell to antigen-mediated degranulation through this pathway can be dramatically influenced by the A2b adenosine receptor. Loss of this G(s)-coupled receptor on mouse bone marrow–derived mast cells results in decreased basal levels of cyclic AMP and an excessive influx of extracellular calcium through store-operated calcium channels following antigen activation. Mice lacking the A2b receptor display increased sensitivity to IgE-mediated anaphylaxis. Collectively, these findings show that the A2b adenosine receptor functions as a critical regulator of signaling pathways within the mast cell, which act in concert to limit the magnitude of mast cell responsiveness when antigen is encountered.